Optoelectronic properties improvement of double perovskites Cs2Sn(Pb)I6 by the hydrothermal method. Issue 8 (6th February 2021) - Wu, Junsheng; Zhao, Zhuo; Li, Tong; Zhang, Kaice; Fang, Fang; Zhou, Yanwen
Abstract: Herein, we report on the synthesis of perovskite Cs2 Sn(Pb)I6 powder via a modified hydrothermal method, in which Pb 2+ ions are introduced to Cs2 SnI6 to optimize the semiconductor properties of double perovskite. Results indicate that the introduction of 2 at% Pb 2+ into the Cs2 SnI6 not only facilitates fine thermal stability, smoother surface with small grain size, expanding the scope of absorption. Thence the photovoltaic properties of Cs2 SnI6 are improved where obtained a higher photocurrent density (∼ 70 µA cm −2 ). Combined with changes in photoelectric properties, perhaps a small amount of Pb doping plays a role in reducing the formation energy and surface energy of the compounds. On the contrary, excessive Pb doping destroys the synthesis of Cs2 SnI6 and reduces the purity of the compound; thus, affecting its application. This study provides useful insights into the development of double perovskites with high stability and efficiency. Abstract : The synthesis of double perovskite Cs2 Sn(Pb)I6 powder is via a modified hydrothermal method, and lead dopant optimize the semiconductor properties of double perovskite. High concentration, low resistivity and wide range of light absorption are exhibited by the Cs2 Sn(Pb)I6 powders. What's more, Cs2 Sn(Pb)I6 obtains a higher photocurrent (∼70 µA cm −2 ).